If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12(y+13)=5(2y-7)
We move all terms to the left:
12(y+13)-(5(2y-7))=0
We multiply parentheses
12y-(5(2y-7))+156=0
We calculate terms in parentheses: -(5(2y-7)), so:We get rid of parentheses
5(2y-7)
We multiply parentheses
10y-35
Back to the equation:
-(10y-35)
12y-10y+35+156=0
We add all the numbers together, and all the variables
2y+191=0
We move all terms containing y to the left, all other terms to the right
2y=-191
y=-191/2
y=-95+1/2
| 6x+6=2x+(-6) | | Y1=4x-2 | | n^2+2n-14.9769=0 | | 4/5y=-7 | | -2z+6=3z+1 | | 2x+5x=8+6 | | 4x+(−9+5x)+16=70 | | 12x-8=20x+16* | | 7y=94.5 | | (3)=6x+100 | | 3x+21=3(11)+21=30+21=51 | | 4x-1+3x+21+90=180 | | 2x+14+3x+21+90=180 | | x2+6x-91=0* | | 11c=78=5c=48 | | 2(5a+4)=48 | | -21=7(7x-24) | | -2(5x+7)=-4 | | -6(4+x)=18 | | m-56=-5 | | 4(2m-7)=3(2m/4) | | 4x-1+6x-4=7 | | 12x^2-68x=-40 | | 12x^2-40x+32=0 | | x−8+8=12 | | (y+18)^2=77 | | 6x-12x=3x+30 | | -(x-1)=-2-4x | | 28-3b=-4(5b-7) | | 2(4x-7)=31-x | | 9(3x-5)=9* | | x–37/9=7 |